Hydrometeorological Short-Range Ensemble Forecasts in Complex Terrain. Part I: Meteorological Evaluation - McCollor, Doug; Stull, Roland (Weather and forecasting, 2008)
This paper addresses the question of whether it is better to include lower-resolution members of a nested suite of numerical precipitation forecasts to increase ensemble size, or to utilize high-resolution members only to maximize forecast details in regions of complex terrain. A short-range ensemble forecast (SREF) system is formed from three models running in nested configurations at 108-, 36-, 12-, and 4-km horizontal grid spacings. The forecasts are sampled at 27 precipitation-gauge locations, representing 15 pluvial watersheds in southwestern British Columbia, Canada. This is a region of complex topography characterized by high mountains, glaciers, fjords, and land–ocean boundaries. Matching forecast–observation pairs are analyzed for two consecutive wet seasons: October 2003–March 2004 and October 2004–March 2005. The northwest coast of North America is typically subject to intense landfalling Pacific cyclones and frontal systems during these months. Using forecast analysis tools that are well designed for SREF systems, it is found that utilizing the full suite of ensemble members, including the lowest-resolution members, produced the highest quality probabilistic forecasts of precipitation. A companion paper assesses the economic value of SREF probabilistic forecasts for hydroelectric operations.